Monitoring of a bridge with integral abutments - Eriksen, Jörgen; Veljkovic, Milan; Nilsson, Martin (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2009)
Preliminary results obtained from short term test-loading are used to illustrate possibilities of FEM used to calibrate complex interaction characteristics between a pile and soil in a bridge with integral abutments. The measurements are obtained during the winter season on the bridge over Leduån, in Northern Sweden. The bridge is built in 2006 and used for long term monitoring within the international project INTAB supported by RFCS. The main objective of the on-going research project is to propose recommendations for rational analysis and design of bridges with integral abutments. Godkänd; 2009; 20091215 (milan)